2002
DOI: 10.1124/jpet.300.2.355
|View full text |Cite
|
Sign up to set email alerts
|

The Ontogeny of Human Drug-Metabolizing Enzymes: Phase I Oxidative Enzymes: Table 1

Abstract: Although some patterns are beginning to emerge, our knowledge of human phase I drug-metabolizing enzyme developmental expression remains far from complete. Expression has been observed as early as organogenesis, but this appears restricted to a few enzymes. At least two of the enzyme families that are expressed in the fetal liver exhibit a temporal switch in the immediate perinatal period (e.g., CYP3A7 to CYP3A4/3A5 and FMO1 to FMO3), whereas others show a progressive change in isoform expression through gesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
180
2
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(193 citation statements)
references
References 34 publications
(48 reference statements)
8
180
2
2
Order By: Relevance
“…The human is a very interesting species with respect to developmental regulation of FMO1 and FMO3. FMO1, the major FMO in liver of most adult mammals, is expressed at relatively high concentrations in human fetal liver, but shortly after birth, expression is reduced to almost zero; the signal for termination of expression is related to the parturition and not to gestational age (Hines & McCarver, 2002;Hines et al, 2003). FMO1 may play an important role in extrahepatic drug metabolism in humans as well as in the liver of the fetus exposed to numerous potential xenobiotic substrates in utero.…”
Section: Genetic Variants and Polymorphisms In Flavin-containing Monomentioning
confidence: 99%
“…The human is a very interesting species with respect to developmental regulation of FMO1 and FMO3. FMO1, the major FMO in liver of most adult mammals, is expressed at relatively high concentrations in human fetal liver, but shortly after birth, expression is reduced to almost zero; the signal for termination of expression is related to the parturition and not to gestational age (Hines & McCarver, 2002;Hines et al, 2003). FMO1 may play an important role in extrahepatic drug metabolism in humans as well as in the liver of the fetus exposed to numerous potential xenobiotic substrates in utero.…”
Section: Genetic Variants and Polymorphisms In Flavin-containing Monomentioning
confidence: 99%
“…We found that the top five major CYP enzymes, which are responsible for ~85% of known oxidative drug metabolism, showed activity in the hEHs, and the most important phase II glucuronidation enzymes were also active ( Figure 1G). Among these enzymes, the expression of CYP1A2 and 2C19 can only be detected well after birth in the human liver [10]. The activities of CYP3A4, 2C9, 2E1 and UGT in the hEHs were comparable to or higher than the activities in 25-week-old fetal hepatocytes.…”
mentioning
confidence: 95%
“…So, total CYP3A protein expression over the entire developmental period remains constant. However, because CYP3A7 and CYP3A4 exhibit differences in substrate specificity and catalytic efficacy, some differences in metabolic capacity during development are observed [8]. If is true that many genes are expressed much more in early life than in adults, is also true that many drug metabolizing enzymes (DME) are less developed in children than in adults.…”
Section: Response To the Drugs: What Is The Difference Between Childrmentioning
confidence: 99%
“…Most reports on the developmental expression of DMEs have limited their studies to short time frames of development, many have depended on a small number of tissue samples, mostly confined to the hepatic expression during fetal development. Furtherome, there is also a paucity of information regarding changes during early childhood or at puberty [8]. While the pharmacogenetics as the study or clinical testing of genetic variation that gives rise to differing response to drugs might be considered similar in adults and children, the 'pharmacogenomics' as the study of how interacting systems of genes determine drug response [12] is particularly appealing in a pediatric and developmental context because this definition captures the essence of the developmental processes that characterize maturation from the time of birth through to adulthood [5].…”
Section: Response To the Drugs: What Is The Difference Between Childrmentioning
confidence: 99%